Penerapan Sistem Informasi Distribusi Bahan Pokok Di Masjid Assalaam Nitikan Kota Yogyakarta - Jumasa, Hamid Muhammad; Saputro, Wahju Tjahjo (INTEK : Jurnal Informatika dan Teknologi Informasi, 2020)
Food as a basic human need whose fulfillment is a basic human right of all Indonesian people must always be available at all times, safe, and diverse at prices that are affordable by people's purchasing power. The issue of scarcity of staple commodities is of serious concern to the Government. The problem is compounded when the community has to implement social restrictions (social distancing) during the Covid-19 disaster response period. During the Covid-19 pan-demic, it had a very broad impact, one of which required residents to worship at their homes during the holy month of Ramadan. The Takmir Mosque of Assalaam Management issued a policy to continue to hold takjil activities. The takjil activity carried out was to provide staples to be distributed to the Assalaam mosque as a menu to break the fast. To support the distribution of staples, community service this time built a web-based information system to manage the distribution of staples for Assalaam Mosque worshipers. This information system is used to monitor the number of recipients of staples, and the distribution is carried out in three stages, at the first stage on April 26, 2020, a number of 173 packages, the second stage on May 5, 2020, a number of 205 packages, and the third stage on May 18, 2020, 205 packages.